Critical thinking in the face of the culture of banality - Sequeiros, Leandro (Razón y fe, 2022)
Our western world is living moments of banality. The recent phenomena of the great health crisis caused by the coronavirus have shown that in the West we do not have the capacity to live solitude and activate the capacity to think. A book by Professor Manuel Fraijó, Semblanzas de grandes pensadores. Conferencias (Madrid, 2020) invites us to open our minds to the various proposals on the meaning of life, calm reflection on reality, experiences of social interaction, spirituality, and transcendence.